Perancangan Sistem Informasi Pencatatan Data Maintenance Barang Sarana Prasarana Di Bagian Rumah Tangga Universitas Sebelas Maret Surakarta - kristanto, dwi (Indonesian Journal of Information Technology and Computing (IMAGING), 2022)
The recording of data on maintenance of facilities and infrastructure at Sebelas Maret University, Surakarta (UNS) is still using a ledger and then copied to Microsoft Excel. The current management of maintenance data causes the making of infrastructure maintenance reports not on time. This has the effect of not being optimal in the care carried out by officers, so that infrastructure facilities are damaged quickly. Based on the description of the problem above, the researcher formulates the problem to be solved in this study, "How to design an information system for recording data on maintenance of infrastructure in the household section of UNS". The method used to design the information system in this research is the System Development Life Cycle (SDLC) with the Waterfall method. This information system is designed using the PHP Native programming language and MySQL database for data storage. The purpose of this research is to design an information system to speed up the preparation of infrastructure maintenance reports, making it easier for leaders to monitor the condition of infrastructure. With the design of this information system, it is hoped that it will facilitate the preparation of infrastructure maintenance reports and monitoring the condition of existing infrastructure at UNS.